2012
DOI: 10.1002/pbc.24386
|View full text |Cite
|
Sign up to set email alerts
|

The association between socioeconomic status and survival among children with Hodgkin and non‐Hodgkin lymphomas in a universal health care system

Abstract: SES was not associated with risk of death among pediatric HL and NHL patients in Ontario. This was consistent through the cancer trajectory, including diagnosis, treatment, and survivorship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 34 publications
2
43
2
Order By: Relevance
“…In our subanalyses for all hematological cancers and for acute lymphoblastic leukemia, we found no effect of socioeconomic position on survival. These results are in line with those of a large study in the US (subset of children 0-14 years; n ¼ 4158) [10], a smaller acute lymphoblastic leukemia study in Germany (n ¼ 788) [9], as well as a Canadian study of lymphomas (n ¼ 692) [11]. In contrast, four smaller European studies (n ¼ 714-1559) found associations between various proxies of parental socioeconomic position and survival after childhood acute lymphoblastic leukemia [5][6][7][8].…”
Section: Comparison With Other Studiessupporting
confidence: 80%
See 2 more Smart Citations
“…In our subanalyses for all hematological cancers and for acute lymphoblastic leukemia, we found no effect of socioeconomic position on survival. These results are in line with those of a large study in the US (subset of children 0-14 years; n ¼ 4158) [10], a smaller acute lymphoblastic leukemia study in Germany (n ¼ 788) [9], as well as a Canadian study of lymphomas (n ¼ 692) [11]. In contrast, four smaller European studies (n ¼ 714-1559) found associations between various proxies of parental socioeconomic position and survival after childhood acute lymphoblastic leukemia [5][6][7][8].…”
Section: Comparison With Other Studiessupporting
confidence: 80%
“…when contemporary cancer therapies were used. Some previous studies included only children with leukemia [5][6][7][8]10], acute lymphoblastic leukemia only [9] or lymphomas [11]. In our subanalyses for all hematological cancers and for acute lymphoblastic leukemia, we found no effect of socioeconomic position on survival.…”
Section: Comparison With Other Studiescontrasting
confidence: 32%
See 1 more Smart Citation
“…Differences in health care systems could, therefore, explain our different results, as the French universal health care system may be better able to obviate barriers to access necessary NHL care, as demonstrated in Canada by Darmawilarta et al . 38 and more recently, in Germany for patients with acute myeloid leukemia. 39 A Scandinavian study also found a relationship between low SES (specifically, educational level) and poor relative survival outcome of NHL patients overall, without any subtype analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these studies failed to account for environmental and socioeconomic differences between the groups. Only a few studies evaluated patients with solid tumors [7,8] and even fewer studies examined the impact of SES or access to care on pediatric cancer burden and outcome [3,912]. …”
mentioning
confidence: 99%